Analysis of spleen of mice (Mus musculus) infected with Aspergillus nidulans identifies immune-related genes. (September 2022) - Xiang, Yi; Emu, Quzhe; Wang, Li; Wei, Yong; Xing, Liu; Zhang, Ling; Wang, Haipeng
Abstract: Aspergillus nidulans ( A. nidulans ) is an ascomycetous fungus that can cause disseminated infection in humans or animals. The present study aimed to explore the pathogenesis and host spleen immune response after infection with A. nidulans . Thirty KM mice were divided into control group (C) and treated group (T). Serum was collected for the detection of inflammatory markers. Spleens were collected for histopathological examination, fungal culture and transcriptomic analysis. Compared with the control group, the concentrations of serum total protein (TP), globulin (GLO) and C-reactive protein (CRP) were significantly increased ( P < 0.01), but the concentration of albumin (ALB) and the ratio of albumin/globulin (A/G) were significantly decreased in the treated group ( P < 0.01). In addition, the splenic red pulp was hyperemic, and the white pulp was infiltrated by inflammatory cells in treated group. The chromatin was aggregated, and the mitochondria were swollen in the spleen lymphocytes of treated group. Transcriptome sequencing results showed that 47.2 million and 44.9 million clean reads were obtained in the control group and treated group, respectively. 946 differentially expressed genes (DEGs) were obtained, including 372 up-regulated genes and 574 down-regulated genes. GO analysis showed that these DEGs were mainly involved in the immune responses, antigen binding, immunoglobulin receptor binding, bacterial defence responses, endopeptidase activity and so on. Moreover, KEGG analysis showed that these DEGs were mainly enriched in the following pathways: complement and coagulation cascades, retinol metabolism, cytochrome p450, IL-17 signalling pathway and so on. Additionally, 9 DEGs was validated by qRT-PCR approach. In summary, this study revealed the immune response mechanism of spleen in A. nidulan -infected mice. It will benefit for a better understanding of the pathogenic mechanisms of A. nidulans . Highlights: Aspergillus nidulans -induced pathological changes in spleen of mice. Immune and inflammation-related DEGs in the infected mice were screened by RNA-Seq analysis. Exploring the possible molecular mechanism of Aspergillus nidulans -induced spleen injury.